2018
DOI: 10.1155/2018/4302062
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Trained Worker Assignment Problem in Cellular Manufacturing System Using Swarm Intelligence Metaheuristics

Abstract: Cross-trained worker assignment has become increasingly important for manufacturing efficiency and flexibility in cellular manufacturing system because of the recent increase in labor cost. Researchers mainly focused on assigning skilled workers to tasks for favorable capacity or cost. However, few of them have recognized the need for skill level enhancement through cross-training to avoid excessive training, especially for workload balance across multiple cells. This study presents a new mathematical programm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
(59 reference statements)
0
4
0
Order By: Relevance
“…Based on the proposed model, it can be concluded that each worker requires a specified amount of time to be trained in the next skill depth level related to the given task, which incurs a training cost. Wu et al (2018a) presented a novel mathematical programming model for addressing the worker assignment problem. In the proposed model, the training cost for each worker for each task depends on the task type and the worker's skill level.…”
Section: Impacts Of Workforce Skill Differences On the Production Costmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the proposed model, it can be concluded that each worker requires a specified amount of time to be trained in the next skill depth level related to the given task, which incurs a training cost. Wu et al (2018a) presented a novel mathematical programming model for addressing the worker assignment problem. In the proposed model, the training cost for each worker for each task depends on the task type and the worker's skill level.…”
Section: Impacts Of Workforce Skill Differences On the Production Costmentioning
confidence: 99%
“…Cross Training costChu et al (2019); Pistolesi (2018a, 2018b);Wu et al (2018a);Niakan et al (2016);Liu et al (2013);Aryanezhad, Deljoo, and Mirzapour Al-e-Hashem (2009a);McDonald et al (2009);Norman et al (2002) Labor costHashemoghli, Mahdavi, and Tajdin (2019);Salehi, Maleki, and Niroomand (2018);Niakan et al (2016);Sungur and Yavuz (2015);Xin et al (2015);Costa, Fichera, and Cappadonna (2013b); Zhang and Gen (2011); Moon, Logendran, and Lee (2009); Kuo and Yang (2007); Wirojanagud et al (2007) Throughput / Productivity / output/ line efficiency Méndez-Vázquez and Nembhard (2019); Digiesi et al (2018); Wu et al (2018b); Öner-Közen, Minner, and Steinthaler (2017); Fattahi, Samoei, and Zandieh (2016); Mossa et al (2016); Bentefouet and Nembhard (2013); Asensio-Cuesta et al (2012); Chen et al (2012); Nanthavanij, Yaoyuenyong, and Jeenanunta (2010); McDonald et al (2009); Nembhard and Shafer (2008); Wirojanagud et al (2007); Song et al (2006); Allwood and Lee (2004); Buzacott (2002); Norman et al (2002); Shafer, Nembhard, and Uzumeri (2001) Workload balancing / smoothing Lian et al (2018); Sadeghi, Rebelo, and Ferreira (2018); Dalle Mura and Dini (2017); Zacharia and Nearchou (2016); Xin et al (2015); Manavizadeh et al (2013) Others: Energy expenditure, job safety, job satisfaction and workers' health Dalle Mura and Dini (2019b); Asensio-Cuesta et al (2012); Aryanezhad et al (2009b) Age Cycle time; task processing time Digiesi et al (2018); Efe, Kremer, and Kurt (2018); Baines et al (2004) Experience Boenzi et al (2015) Throughput / Productivity / output/ line efficiency Digiesi et al (2018); Efe, Kremer, and Kurt (2018); Börsch-Supan and Weiss (2016); Baines et al (2004);Quintana, Leung, and Chen (2008) …”
mentioning
confidence: 99%
“…DRC system is a manufacturing system, which is not only constrained by machine capacity, but also by workforce capacity. Cross-trained workforce is also largely used in CMS (Slomp et al, 2005;Kaku et al, 2008;Aryanezhad et al, 2009;Wu et al, 2018;Chu et al, 2019).…”
Section: Cross-trained Workersmentioning
confidence: 99%
“…In recent years, several authors have investigated the impacts of cross-training and workforce skill levels on economic and human issues. Wu et al [9] explored the trade-off between skill training cost and workload balance by proposing a swarm intelligence optimizer. Their proposed algorithm generates a better solution than the candidate algorithm.…”
Section: Cross-training Workforce and Skill Levelmentioning
confidence: 99%